Community perceptions of pre-eclampsia and eclampsia in southern Mozambique. Issue 1 (June 2016) - Boene, Helena; Vidler, Marianne; Sacoor, Charfudin; Nhama, Abel; Nhacolo, Ariel; Bique, Cassimo; Alonso, Pedro; Sawchuck, Diane; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; et al.
Abstract Background Sub-Saharan Africa has the highest maternal mortality ratio at 500 deaths per 100, 000 live births. In Mozambique maternal mortality is estimated at 249-480 per 100, 000 live births and eclampsia is the third leading cause of death. The objective of this study was to describe the community understanding of pre-eclampsia and eclampsia, as a crucial step to improve maternal and perinatal health in southern Mozambique. Methods This qualitative study was conducted in Maputo and Gaza Provinces of southern Mozambique. Twenty focus groups were convened with pregnant women, partners and husbands, matrons and traditional birth attendants, and mothers and mothers-in-law. In addition, ten interviews were conducted with traditional healers, matrons, and a traditional birth attendant. All discussions were audio-recorded, translated from local language (Changana ) to Portuguese and transcribed verbatim prior to analysis with QSR NVivo 10. A thematic analysis approach was taken. Results The conditions of "pre-eclampsia" and "eclampsia" were not known in these communities; however, participants were familiar with hypertension and seizures in pregnancy. Terms linked with the biomedical concept of pre-eclampsia werehigh blood pressure, fainting disease andillness of the heart, whereasillness of the moon, snake illness, falling disease, childhood illness, illness of scares andepilepsy were used to characterizeeclampsia. The causes of hypertension in pregnancy were thought to include mistreatment by in-laws, marital problems, and excessive worrying. Seizures in pregnancy were believed to be caused by a snake living inside the woman's body. Warning signs thought to be common to both conditions were headache, chest pain, weakness, dizziness, fainting, sweating, and swollen feet. Conclusion Local beliefs in southern Mozambique, regarding the causes, presentation, outcomes and treatment of pre-eclampsia and eclampsia were not aligned with the biomedical perspective. The community was often unaware of the link between hypertension and seizures in pregnancy. The numerous widespread myths and misconceptions concerning pre-eclampsia and eclampsiamay induceinappropriatetreatment-seeking and demonstrate a need for increased community education regarding pregnancy and associated complications. Trial Registration NCT01911494 Resumo Antecedentes A África Subsaariana tem a taxa de mortalidade materna mais alta, com cerca de 500 mortes por 100.000 nascidos vivos. Em Moçambique a mortalidade materna é estimada em 249-480 por 100.000 nascidos vivos e a eclâmpsia é a terceira causa de morte. O objectivo deste estudo foi de descrever o que as comunidades entendem por pré-eclâmpsia e eclâmpsia, como uma etapa crítica para melhorar a saúde materna e perinatal no sul de Moçambique. Métodos Este estudo qualitativo foi realizado nas Províncias de Maputo e Gaza no sul de Moçambique. Vinte discussões em grupos focais foram organizadas com mulheres grávidas, parceiros e maridos, matronas e parteiras tradicionais, mães e sogras. Adicionalmente, dez entrevistas em profundidade foram feitas com praticantes de medicina tradicional, matronas e parteiras tradicionais. Todas as entrevistas e discussões foram áudio-gravadas, traduzidas da língua local (Changana ) para Português e transcritas na íntegra antes da análise com QSR NVivo 10. Foi usada uma abordagem de análise temática. Resultados As condições de "pré-eclâmpsia " e "eclâmpsia " não eram conhecidas nestas comunidades; contudo, os participantes estavam familiarizados com hipertensão e convulsões na gravidez. Os termos ligados a conceitos biomédicos de pré-eclâmpsia eram tensão alta, desmaios e doença do coração; enquanto doença da lua, doença da cobra, doença de queda, doença de infância, doença de sustos e epilepsia eram os termos usados para caracterizar a eclâmpsia. Localmente, pensa-se que as causas de hipertensão na gravidez incluem maus tratos por parte dos sogros, problemas conjugais e excesso de preocupações. Em relação as convulsões na gravidez, acredita-se que sejam causadas por uma cobra que vive dentro do corpo da mulher. Os sinais de perigo que se pensa serem comuns as duas condições eram dor de cabeça, dor do peito, fraqueza, tonturas, desmaios, sudação e pernas inchadas. Conclusão Crenças locais no sul de Moçambique em relação as causas, apresentação, resultados e tratamento da pré-eclâmpsia e eclâmpsia não estavam alinhadas com a perspectiva biomédica. A comunidade muitas vezes não tinha conhecimento da ligação entre a hipertensão e as convulsões na gravidez. Os numerosos e generalizados mitos e falsos conceitos relativos a pré-eclâmpsia e eclâmpsia podem levar a tratamento inapropriado – exigindo e demonstrando a necessidade de reforço na educação da comunidade em relação a gravidez e complicações associadas. Registo do ensaio NCT01911494